Membangun Jiwa Kewirausahaan dengan Kegiatan Unggulan Koperasi Mahasiswa UNY Mengembangkan Potensi Mahasiswa di Berbagai Bidang - Fastiani, Afria Eky; Rahmadani, Nurulita Fina; Wijayanti, Agustina Tri; Dhewantoro, Happri Novriza Setya (CV ODIS, 2025)
Student cooperatives, as a member-based economic forum, which not only meets the daily needs of students, but student cooperatives can be a mini laboratory for prospective entrepreneurs. However, in carrying out its operations, student cooperatives are often faced with various obstacles. This research will reveal how student cooperatives can be an effective means to foster the entrepreneurial spirit of students, as well as identify the challenges.